Perencanaan Strategis Sistem Informasi pada Aplikasi Medical Contact berbasis Mobile Menggunakan Framework Ward and Peppard dan Task-Centered Design Process - Anang Kunaefi; Silvia Nandasari; Clarissa Luthfia Rachmad; Nur Isnaini (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2021)
Health awareness is an important aspect of today's society with a pandemic. This condition also causes people to feel anxious when they want to visit the hospital. As a result, many online-based home care services emerged. This research proposes a technological innovation called Medical Contact, a digital platform prototype to bring together medical personnel such as doctors, nurses, and patients in real time even though they are in different locations. With this platform, patients are able to submit complaints and obtain health solutions from doctors efficiently. Prototyping is done using an information system strategic planning approach using the Ward and Peppard framework. In addition, the Task Centered Design method is used to design UI/UX applications. The steps in the process consist of analyzing the business environment, performing tasks and user analysis, selecting representative tasks for task-centric designs, plagiarizing, and prototyping. The results obtained are an application prototype with features, a user interface, and a user experience according to user needs that are in line with business goals.